2002
DOI: 10.1207/s15327957pspr0601_1
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Coping Behavior: A Meta-Analytic Review and an Examination of Relative Coping

Abstract: We used meta-analysis to examine recent studies of sex differences in coping. Women were more likely than men to engage in most coping strategies. The strongest effects showed that women were more likely to use strategies that involved verbal expressions to others or the self—to seek emotional support, ruminate about problems, and use positive self-talk. These sex differences were consistent across studies, supporting a dispositional level hypothesis. Other sex differences were dependent on the nature of the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

163
1,005
24
39

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 1,376 publications
(1,281 citation statements)
references
References 109 publications
163
1,005
24
39
Order By: Relevance
“…Separate from the kind and intensity of the stressors is the appraisal of stressors. Just as there are gender differences in stressor appraisalwomen usually appraise stressors as more serious then men (Tamres et al, 2002)-there might also be sexual orientation-related differences in the appraisal of specific stressors. Further research should explore this.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Separate from the kind and intensity of the stressors is the appraisal of stressors. Just as there are gender differences in stressor appraisalwomen usually appraise stressors as more serious then men (Tamres et al, 2002)-there might also be sexual orientation-related differences in the appraisal of specific stressors. Further research should explore this.…”
Section: Discussionmentioning
confidence: 99%
“…The actual relationship between gender and coping style does, however, seem to be more complex and should also acknowledge the social roles both genders are in (Rosario, Shinn, Morch, & Carol, 1988;Sigmon et al, 1995). Furthermore, gender also seems to affect whether specific coping styles have positive or negative health effects (Endler & Parker, 1994;Higgins & Endler, 1995;Hobfoll, Dunahoo, Ben-Porath, & Monnier, 1994;Recklitis & Noam, 1999;Tamres, Janicki, & Helgeson, 2002). Higgins and Endler (1995), for instance, showed that task-oriented coping was negatively related to distress for men but not for women.…”
Section: Introductionmentioning
confidence: 99%
“…Šio tyrimo kiekybinių duomenų analizės rezultatai atitinka kitų tyrimų rezultatus, kurie rodo didesnį moterų polinkį taikyti įvairias įveikas (Tamres et al, 2002). Taip pat galime matyti, kad moterys dažniau nei vyrai ieško socialinės paramos, o vyrai sunkumus stengiasi įveikti patys, be kitų pagalbos.…”
Section: Rezultatų Aptarimasunclassified
“…Taip pat galime matyti, kad moterys dažniau nei vyrai ieško socialinės paramos, o vyrai sunkumus stengiasi įveikti patys, be kitų pagalbos. Tai sutampa su kitų tyrimų rezultatais (Tamres et al, 2002;Möller-Leimkühler, 2002).…”
Section: Rezultatų Aptarimasunclassified
See 1 more Smart Citation